Influence of telemetry on the competitiveness of the virtual gas pipeline transportation service - Zamudio Ortega, Jandy Aledis (2021)
The investigative purpose of this article is to determine the influence of the telemetry system on the competitiveness of the Virtual Gas Pipeline (GNC) transportation service, since telemetry allows us to optimize the performance of operations, facilitating the management of the company, increasing productivity. using the Supervisory Control And Data Acquisition (SCADA) and Global Positioning (GPS) system. For this, the methodology used is applied type, with a quantitative approach, a non-experimental cross-sectional design, in addition, its method is hypothetical-deductive and develops a correlational level. For this research, a survey-type instrument was applied to a sample of 31 clients of the El Gran Z transport company, which was reviewed and certified by expert judgment, Cronbach in 0.966; this value indicates that it is highly reliable. The result of this research is that there is a significant influence of the telemetry system (SCADA and GPS) on the competitiveness of the CNG transportation service.